Effect of storage time and concentration of used cooking oil on polyhydroxyalkanoates (PHAs) production by Cupriavidus necator H16 - Chatsuda Kongpeng,; Jutarut Iewkittayakorn,; Wilaiwan Chotigeat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Polyhydroxyalkanoates (PHAs) can be used to replace petrochemical plastics in many applications. However, their production has limitation due to production cost. This research was conducted using alternative carbon source from waste to synthesize PHAs by Cupriavidus necator H16. In this study, PHAs were produced from used cooking oil (UCO) and compared with production PHAs from palm oil. Two UCO storage times (4 and 10 weeks) and three UCO concentrations (10, 20 and 30 g/L) were used to determine the most optimum condition for PHA synthesis. The best optimum condition for PHA synthesis was cultivated in the medium containing 30 g/L of UCO at 4 weeks storage. The cell dry weight (CDW) and PHA content were 5.26±0.61 g/L and 27.36±2.04 wt. %, respectively. These results were similar to cell cultivation using 20 g/L palm oil and 1% of fructose (5.93±0.33 g/L of CDW and 26.96±6.14 wt. % of PHA contents). In addition, PHA content from the culture with 10 g/L of UCO stored for 10 weeks was higher than PHA content from the culture with 20 and 30 g/L of UCO. Thus, it can be concluded that UCO could be used in PHA production.